Efficacy and safety of sofosbuvir-based antiviral therapy to treat hepatitis C virus infection after kidney transplantation - Reddy, Suresh (Clin Kidney J, 2018)
BACKGROUND: The objectives of this pilot study were to assess the efficacy and safety of an interferon-free sofosbuvir and ribavirin combination regimen to treat chronic hepatitis C virus (HCV) infection in kidney transplant recipients and to study the impact of sofosbuvir on calcineurin inhibitor (CNI) drug levels. METHODS: A total of 10 kidney transplant recipients with chronic HCV infection were included in the study. All received sofosbuvir and ribavirin combination therapy. The virological response to therapy and the adverse effects of the drugs were studied. The area under the curve (AUC) and pharmacokinetic data of levels of CNI were compared while the patients were receiving sofosbuvir and ribavirin drugs and when they were no longer on these drugs. RESULTS: In all, 9 of 10 patients (90%) achieved rapid virological response (RVR) with undetectable HCV RNA at 4 weeks and the remaining patient achieved undetectable HCV RNA at 8 weeks. A sustained virological response was seen at 3, 6 and 12 months and was maintained in all 10 patients (100%). The important aspect of the study is the effect of treatment with the sofosbuvir–ribavirin combination regimen on the CNI AUC levels, which resulted in a reduction in the CNI AUC. While used as part of triple-drug immunosuppression, no change in the dose of CNI (tacrolimus and cyclosporine) was required based on measurement of C0 levels. CONCLUSIONS: The sofosbuvir and ribavirin combination therapy is effective and safe to treat HCV infection in the post-renal transplant setting. There is a need for close CNI level monitoring while these patients are on sofosbuvir therapy. With therapy and viral clearance, there could be reduction in CNI levels due to increased clearance of CNI drugs, which is shown by the AUC measurements. This could be important for patients at high risk for rejection.